THE INCIDENCE OF HEART DISEASE IN MEXICO A STUDY OF 2400 CASES OF ORGANIC HEART DISEASE - CHAVEZ, IGNACIO (HOSPITAL GENERAL, CD. MEXICO, DF, MEX, 1942)
Several statistical studies on heart disease have been published recently. Those from the United States, England, Czechoslovakia, and Argentina are particularly extensive and interesting. They inquire into the real importance of the different causes of or
AM HEART J
Keywords: INCIDENCE, HEART, DISEASE, MEXICO, STUDY, CASES, ORGANIC; CIENCIAS MEDICAS; MEDICINA INTERNSA; CARDIOLOGIA